2008
DOI: 10.1002/pbc.21465
|View full text |Cite
|
Sign up to set email alerts
|

Low prevalence and assay discordance of “aspirin resistance” in children

Abstract: In this initial prevalence study of a clinically diverse group of pediatric patients, frequencies of AR were assay-dependent; however, the prevalence of true AR is likely low in children (2.3%; 95% CI 0.1-10.7%), in agreement with adult studies. To better define the clinical relevance of AR in children, multicenter, prospective cohort studies are imperative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…Previous studies have suggested that the incidence of true aspirin resistance in children is approximately 2% and that many patients respond to an appropriate increase in aspirin dosing. 4,9 Future studies should determine if dose adjustment, particularly in neonates and pediatric patients greater than 80 kg, improves responsiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that the incidence of true aspirin resistance in children is approximately 2% and that many patients respond to an appropriate increase in aspirin dosing. 4,9 Future studies should determine if dose adjustment, particularly in neonates and pediatric patients greater than 80 kg, improves responsiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Six out of 44 were considered aspirin resistant according to at least one laboratory test (5 by PFA-100, 1 by aggregometry, and urinary 11dhTxB2), which leads to the conclusion that, as with adults, the incidence of AR is also assay-dependent in the pediatric population [31]. Table 1 summarizes the main studies investigating AR prevalence in different clinical entities [28, 30, 3236].…”
Section: How Prevalent Is Aspirin Resistance?mentioning
confidence: 99%
“…81 Yee et al have recently reported their investigation of aspirin resistance in 44 children using several different assays: platelet aggregation, PFA-100 closure time, and urinary 11-dehydro thromboxane B 2 . 82 Six patients showed evidence of in vitro resistance in one of the assays, but there was poor correlation among the assays, and no clinical correlation was reported. The identification of a clinically relevant assay for children requires further study.…”
Section: Investigation Of Acquired Platelet Function Disordersmentioning
confidence: 96%